PRODUCTION MUTANT LINES OF TURNIP RAPE (BRASSICA RAPA) AND ITS INTERSPECIFIC HYBRIDS IN THE ISOLATED MICROSPORE CULTURE (Experimental biology, 2022)
This article presents the results of research on the production of mutant doubled haploids of turnip rape (Brassica rapa L.ssp.Oleifera), as well as its interspecies hybrids with rapeseed (Brassica napus). An  immature embryo culture  was used to increase the productivity of inter-specific hybridization. Studies have obtained interspecific hybrids of turnip rape with rapeseed. The largest number of plants was observed in hybrids where the mother plant was rapeseed. Furthermore, chemical mutagenesis was used to increase the genetic diversity of studied materials. Ethyl methanesulfonate (EMS) has been applied to the treatment of embryos produced in the isolated microspores culture  of turnip rape and its interspecies hybrids. Results of embryo regeneration against mutagen on a nutrient medium B5 with gibberellic acid showed that the concentration of 8 mM EMS stimulated the regeneration process in turnip rape cultivars (Zolotistaya - 72% and Yantarnaya - 88%) and showed superior results compared to a low concentration (4 mM). For hybrids compared to high concentration (8mM), a low concentration of 4mM EMS showed superior results. New mutant lines have been obtained as the starting material for selection in the creation of new domestic canola cultivars.
Keywords: turnip rape, rapeseed, interspecific hybridization, mutagenesis, isolated microspore culture